Solve for x (X+3)^2 O x^2+3x+2 O 2x^2+3x+2 O x^2 + 6x + 2 O x^2 + 6x +9

Elementary Geometry For College Students, 7e
7th Edition
ISBN:9781337614085
Author:Alexander, Daniel C.; Koeberlein, Geralyn M.
Publisher:Alexander, Daniel C.; Koeberlein, Geralyn M.
ChapterP: Preliminary Concepts
SectionP.CT: Test
Problem 1CT
icon
Related questions
Question
100%
Th question is in the image.
**Transcription for Educational Website:**

---

**Solve for x**

\((x+3)^2\)

- ○ \(x^2 + 3x + 2\)
- ○ \(2x^2 + 3x + 2\)
- ○ \(x^2 + 6x + 2\)
- ○ \(x^2 + 6x + 9\)

---

**Explanation:**

You are asked to expand the expression \((x+3)^2\). To do this, apply the algebraic identity \((a+b)^2 = a^2 + 2ab + b^2\). In this case, \(a = x\) and \(b = 3\). 

Calculating:
- \(a^2 = x^2\)
- \(2ab = 2 \cdot x \cdot 3 = 6x\)
- \(b^2 = 3^2 = 9\)

So, \((x+3)^2 = x^2 + 6x + 9\).

Therefore, the correct option is the last one: \(x^2 + 6x + 9\).
Transcribed Image Text:**Transcription for Educational Website:** --- **Solve for x** \((x+3)^2\) - ○ \(x^2 + 3x + 2\) - ○ \(2x^2 + 3x + 2\) - ○ \(x^2 + 6x + 2\) - ○ \(x^2 + 6x + 9\) --- **Explanation:** You are asked to expand the expression \((x+3)^2\). To do this, apply the algebraic identity \((a+b)^2 = a^2 + 2ab + b^2\). In this case, \(a = x\) and \(b = 3\). Calculating: - \(a^2 = x^2\) - \(2ab = 2 \cdot x \cdot 3 = 6x\) - \(b^2 = 3^2 = 9\) So, \((x+3)^2 = x^2 + 6x + 9\). Therefore, the correct option is the last one: \(x^2 + 6x + 9\).
Expert Solution
trending now

Trending now

This is a popular solution!

steps

Step by step

Solved in 2 steps with 1 images

Blurred answer